2023
DOI: 10.3390/brainsci13010113
|View full text |Cite
|
Sign up to set email alerts
|

Speech and Nonspeech Parameters in the Clinical Assessment of Dysarthria: A Dimensional Analysis

Abstract: Nonspeech (or paraspeech) parameters are widely used in clinical assessment of speech impairment in persons with dysarthria (PWD). Virtually every standard clinical instrument used in dysarthria diagnostics includes nonspeech parameters, often in considerable numbers. While theoretical considerations have challenged the validity of these measures as markers of speech impairment, only a few studies have directly examined their relationship to speech parameters on a broader scale. This study was designed to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…A review of the literature focusing on the issues shows that research evaluating the character of speech disorders in MS is limited (15,23). The available dysarthria scales are based on more or less subjective data, which are more difficult to compare (15,(18)(19)(20)(21)(22)(23). As noted in the review article by Noffs et al objective speech assessment is more accurate, replicable, and feasible when contrasted with perceptual analysis (25) which occurs in the majority of the studies concerning the notion of dysarthria in the course of neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature focusing on the issues shows that research evaluating the character of speech disorders in MS is limited (15,23). The available dysarthria scales are based on more or less subjective data, which are more difficult to compare (15,(18)(19)(20)(21)(22)(23). As noted in the review article by Noffs et al objective speech assessment is more accurate, replicable, and feasible when contrasted with perceptual analysis (25) which occurs in the majority of the studies concerning the notion of dysarthria in the course of neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The Speech Pathology Specific Questionnaire for people with MS has also been developed and validated (7). Based on the review of the world literature, it can be concluded that in many countries the following scales are most often used in phoniatric practice: Vocal Tract Discomfort, GRBAS listening scale, Voice Handicap Index (18)(19)(20)(21). All of the above-mentioned scales are subjective tools, and therefore they are burdened with a certain margin of error, thirdly, they do not allow for the unequivocal distinction between physiological and pathological values, therefore they are of limited use in routine clinical examinations of the vocal organ and do not accentuate on the mechanisms inducing the phenomenon of dysarthria, which is crucial in conducting therapy (22).…”
Section: Introductionmentioning
confidence: 99%
“…Time's influence on lexical and syntactic processing in individuals with aphasia was explored [14]. The use of dimensional analysis to assess dysarthria highlights its importance for a nuanced evaluation of the speech disorder [15]. The study investigated the link between verbal short-term memory deficits in aphasic individuals and word processing impairments.…”
Section: Prior Research Workmentioning
confidence: 99%
“…Although widely used in motor speech assessments, DDK is still a subject of debate. Some studies propose that there is insufficient empirical evidence that would support the clinical use of nonspeech parameters in analyzing motor speech in patients with neurological disorders [23], while others suggest that DDK performance mirrors speech proficiency [24].…”
Section: Introductionmentioning
confidence: 99%